Development of Preserved Invertebrate Specimens for Enhancing Biology Laboratory Learning at Timor University - Mohamad Fajar Farid Amrulloh; Fitra Ramadhan (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Laboratories play an important role in biology learning, especially in specimen observation-based practicums. However, the Biology Education Laboratory at Timor University does not yet have preserved invertebrate specimens as supporting media, necessitating the development of alternative learning media. This study aims to develop preserved invertebrates to improve the quality of invertebrate zoology practicums. The development was carried out using the ADDIE model, including analysis through needs surveys, media design with sampling and design preparation, development through expert validation and revision processes, implementation in practicums through pretests, posttests, and student response questionnaires, and summative evaluation to assess the effectiveness of the media. The evaluation results showed an increase in student understanding after using preserved invertebrate media, so this development was considered effective in supporting practicum activities and improving the quality of biology learning at Timor University. The result development of preservation media for invertebrate animals has been successfully carried out through validity test by material expert tests (84%), media expert tests (80%). Preservation media for invertebrate animals has a high practicality value (82%) & high effectiveness (80%). The different pretest rate (65) and posttest rate (84,5) results are quite significant and have a correlation due to the presence of preservation media for invertebrate animals.